VD_FINDINFO HC / 2021 / 145 vom 30. März 2021 - VD Tribunal cantonal (2021)
CONTRAT D'ENTREPRISE, SOUS-TRAITANT, PRIX EFFECTIF, PRIX DU MARCHÉ, DÉPENS, FRAIS JUDICIAIRES | 8 CC, 374 CO, 106 al. 2 CPC (CH), 94 CPC (CH)